2010
DOI: 10.1007/s11538-010-9602-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolizing Enzyme Activities Modulated by Phospholipid Substrate Lateral Distribution

Abstract: Biological membranes contain many domains enriched in phospholipid lipids and there is not yet clear explanation about how these domains can control the activity of phospholipid metabolizing enzymes. Here we used the surface dilution kinetic theory to derive general equations describing how complex substrate distributions affect the activity of enzymes following either the phospholipid binding kinetic model (which assumes that the enzyme molecules directly bind the phospholipid substrate molecules), or the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The above kinetics expressions can be generalized to any amount of substrate domains, even to infinite number of domains, and this latter is very useful for modeling any kind of substrate distribution in the total lipid phase [22].…”
Section: Lypolitic Enzyme Activity In Lipid Phases With Multiple Subsmentioning
confidence: 99%
See 2 more Smart Citations
“…The above kinetics expressions can be generalized to any amount of substrate domains, even to infinite number of domains, and this latter is very useful for modeling any kind of substrate distribution in the total lipid phase [22].…”
Section: Lypolitic Enzyme Activity In Lipid Phases With Multiple Subsmentioning
confidence: 99%
“…Defining α as the average number of lipid molecules per lipid particle (in micellar case, this parameter is known as aggregation number), and according to Eq. 17 and Poisson-distributed substrate, it can be demonstrated that [22]…”
Section: Effects Of Poisson Distribution Of Substrate On Enzyme Activmentioning
confidence: 99%
See 1 more Smart Citation